Conducting Polymer Hybrids - Kumar, Vijay; Kalia, Susheel; Swart, Hendrik C. (Springer International Publishing : Imprint: Springer, 2017)
This book presents a comprehensive survey about conducting polymers and their hybrids with different materials. It highlights the topics pertinent to research and development in academia and in the industry. The book thus discusses the preparation and characterization of these materials, as well as materials properties and their processing. The current challenges in the field are addressed, and an outline on new and even futuristic approaches is given. "Conducting Polymer Hybrids" is concerned with a fascinating class of materials with the promise for wide-ranging applications, including energy generation and storage, supercapacitors, electronics, display technologies, sensing, environmental and biomedical applications. The book covers a large variety of systems: one-, two-, and three-dimensional composites and hybrids, mixed at micro- and nanolevel.- Resumé vydavatel
Keywords: elektrochemie; nanochemie; optické materiály; polymery; electrochemistry; nanochemistry; optical materials; polymers; elektronické knihy; kolektivní monografie; electronic books; collective monographs